THE INFLUENCE OF LEADERSHIP, MOTIVATION, ORGANIZATIONAL CULTURE ON JOB SATISFACTION AND PERFORMANCE IN THE SERVICE OF POPULATION AND CIVIL REGISTRATION ROKAN HILIR DISTRICT - ,; ,; ,; ,; , (LUCRUM : Jurnal Bisnis Terapan; Vol 5 No 2 (2025): LUCRUM : Jurnal Bisnis Terapan, 2025)
This study aims to analyze the influence of Leadership, Motivation and Organizational Culture on Job Satisfaction and Performance in the Department of Population and Civil Registration of Rokan Hilir Regency. This research is a quantitative research by distributing questionnaires to respondents. The population of this study were all employees at the Department of Population and Civil Registration of Rokan Hilir Regency. Selection of the sample using the census method, so that the sample in this study amounted to 50 respondents. Data analysis using the Smart PLS 4 application. The results of this study indicate that leadership has a positive and significant effect on job satisfaction and insignificant effect on performance. Motivation has a positive and insignificant effect on job satisfaction and performance. Organizational Culture has a positive and significant effect on job satisfaction and insignificant effect on performance. Job Satisfaction has a positive and insignificant effect on performance.